Correlation between Maternal Lactate Dehydrogenase Levels and APGAR Scores in Preeclampsia Patients at Margono Soekarjo Hospital from 2022–2024 - Bagas Satriyo Wicaksono; Aditiyono Aditiyono; Hadi Susiarno; Dina Marlina; Grazielle Grazielle (Indonesian Journal of Obstetrics & Gynecology Science, 2026)
Objective: This study aims to investigate the correlation between maternal lactate dehydrogenase (LDH) levels and neonatal APGAR scores in preeclamptic patients.Methods: This is an observational analytic study with a cross-sectional design conducted at Margono Soekarjo Hospital from January 2022 to May 2024, involving 78 women with preeclampsia who underwent cesarean delivery. Participants were categorized into early-onset (<34 weeks) and late-onset (≥34 weeks) preeclampsia groups. LDH levels and APGAR scores were analyzed using Spearman’s correlation and ROC analysis.Results: This study showed that elevated LDH levels were significantly associated with lower one-minute APGAR scores, showing moderate correlations in both groups, and were related to five-minute APGAR scores. The LDH cut-off points predicting poor one-minute APGAR outcomes were 284 IU/L (sensitivity 82.1%, specificity 66.7%) for early-onset and 491.5 IU/L (sensitivity 44.4%, specificity 96.2%) for late-onset preeclampsia.Conclusion: Elevated maternal LDH levels are associated with lower one-minute APGAR scores in preeclamptic patients, especially in early-onset cases, indicating they may serve as an early marker for fetal hypoxia and asphyxia risk. AbstrakTujuan: Penelitian ini bertujuan untuk meneliti hubungan antara kadar laktat dehidrogenase (LDH) maternal dan skor APGAR neonatus pada pasien preeklampsia.Metode: Penelitian ini merupakan studi analitik observasional dengan desain potong lintang yang dilakukan di RSUD Margono Soekarjo pada Januari 2022 hingga Mei 2024, melibatkan 78 wanita dengan preeklampsia yang menjalani persalinan melalui seksio sesarea. Peserta dibagi menjadi dua kelompok, yaitu preeklampsia onset dini (<34 minggu) dan onset lambat (≥34 minggu). Kadar LDH dan skor APGAR dianalisis menggunakan korelasi Spearman dan analisis ROC.Hasil: Hasil penelitian ini menunjukkan bahwa peningkatan kadar LDH berhubungan signifikan dengan skor APGAR satu menit yang lebih rendah, menunjukkan korelasi sedang pada kedua kelompok, serta menandai adanya kaitan dengan skor APGAR lima menit. Titik potong kadar LDH yang memprediksi hasil APGAR satu menit yang buruk adalah 284 IU/L (sensitivitas 82,1%, spesifisitas 66,7%) untuk preeklampsia onset dini dan 491,5 IU/L (sensitivitas 44,4%, spesifisitas 96,2%) untuk onset lambat.Kesimpulan: Kadar LDH maternal yang meningkat berhubungan dengan penurunan skor APGAR satu menit pada pasien preeklampsia, terutama pada kasus onset dini. Hal ini menunjukkan bahwa LDH dapat berfungsi sebagai penanda dini risiko hipoksia dan asfiksia janin.